Efektivitas Penggunaan Bahan Ajar Digital Berbasis Android dalam Pembelajaran IPA pada Siswa Berkebutuhan Khusus - Maskur, Maskur; Safitri, Erna Retna (JOEAI (Journal of Education and Instruction), 2021)
This study aims to determine the effectiveness of using Android-based digital teaching materials in science learning for students with special needs. This research is a qualitative research which conducted on respondents, namely students with special needs at the Special Secondary School level. Data collection was carried out using test instruments. Data collection was carried out by giving tests to students and questionnaires to teachers. The collected data were analyzed descriptively quantitatively. The analysis is carried out by providing an interpretation of the data obtained so that it becomes clearer and more meaningful. The results showed that Android-based digital teaching materials were causing an increase in students learning outcomes in this subject by 83.3 percent. The study showed that android-based digital teaching materials effectively used in science learning for students with special needs. Further research is needed using more varied media and a wider scale of research. Keywords: Teaching materials, android, students with special needs.